Performance and Organizational Adaptation Improvement of Private Course and Training Institutions - Pamungkas, Alim Harun; Rasyad, Ach.; ., Zulkarnain; Wahyuni, Sri (Journal of Ecohumanism, 2025)
Interactions among culture, commitment, and organizational adaptation play a significant role in non-formal educational organizations, such as private courses and training institutions. These factors are crucial for maintaining and enhancing organizational performance. This research examines the organizational dynamics within private course and training institutions in Indonesia, focusing on how strategic management and work engagement directly contribute to organizational success and adaptability. By integrating quantitative assessments with a comprehensive theoretical framework, this study aims to provide a deeper understanding of the factors driving the successful adaptation of private course and training institutions in Indonesia amidst increasing global competition and technological advancements. Through this exploration, the research seeks to offer strategic insights and best practices for non-formal educational organizations in similar contexts. This research surveyed approximately 500 staff members from various Private Course and Training Institutions (PCTIs) across Indonesia, selected through systematic sampling from an estimated population of 576 to 960 individuals working in 192 PCTIs. A structured questionnaire, consisting of both closed and open-ended questions, was used to collect quantitative data regarding their perceptions of key organizational factors. The analysis techniques employed included multiple regression, path analysis, and Structural Equation Modeling (SEM) to explore the relationships between variables and understand organizational dynamics within these institutions. The results indicate several significant direct impacts among the variables. Work Engagement (X6) demonstrates a strong and statistically significant impact on Organizational Adaptation (Y3) with a path coefficient of 0.470 (p < 0.001), indicating a substantial direct effect. Organizational Learning (X4) also shows a significant impact on Work Engagement (X6) with a high coefficient of 0.660 (p < 0.001), and on Organizational Adaptation (Y3) with a coefficient of 0.228 (p = 0.014). Knowledge Transfer (X5) has a considerable direct impact on Organizational Adaptation (Y3) and Performance (Y1 and Y2) with coefficients ranging from 0.078 to 0.119, all of which are statistically significant. Conversely, the impact of Organizational Culture (X3) on Organizational Adaptation (Y3) is very weak and not significant (coefficient = 0.010, p = 0.651).